Seroprevalence and preliminary treatment of toxoplasmosis of pregnant goats in Kalubyia Governorate, Egypt - Mohamed Youssif Ramadan (Acta Scientiae Veterinariae, 2007)
Toxoplasmosis is a zoonotic disease that commonly infects goat in Egypt. For its diagnosis, sera form 48 pregnant does were tested for Toxoplasma gondii antibodies through indirect haemagglutination test (IHAT) and modified agglutination test (MAT). Samples were collected between the periods extended from November 2006 to March 2007. The seropositive rate of pregnant does (Meet Kenana, Kalubyia Governorate, Egypt) was 35.42% (17/48). After using MAT test against T. gondii- IgM, 11 sera (22.9%) were found positive. The older animals were more frequently infected (50%) than the younger goats (26.3%). Higher prevalence in aged does was confirmed by MAT. Total T.gondii antibodies and IgM were gradually increased with the development of pregnancy. Two months post treatment with sulfademidine 33.3 %, for 5 successive days at a dose of 200 mg/kg, resulted in not only reduction of T.gondii total antibodies and IgM in all treated does, but re-modulation of T.gondii antibody titres moderately toward the mild titres, and prevention of congenital infection and abortion as well. Whereas IgM was not recorded in treated does, it was detected in the untreated ones. No abortion was recorded in all treated does, but an untreated doe delivered two dead fetuses. The delivered kids belonged to treated does were seropositive for T. gondii antibodies by using IHAT, yet they were seronegative for T.gondii' IgM by using MAT. In contrast, kids belonged to untreated does were seropositive by using both IHAT and MAT. Adequate management might be useful and essential to control toxoplasmosis in the goat herds of Kalubyia Governorate.